2009
DOI: 10.1007/s10815-009-9346-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage impairs global sperm DNA methylation in infertile men

Abstract: These results suggest that oxidative stress related damage to sperm DNA impedes the process of methylation, while antioxidant supplementation appears to have the potential to reduce DNA damage and normalize sperm DNA methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
179
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(186 citation statements)
references
References 55 publications
4
179
1
1
Order By: Relevance
“…A study of 45 infertile men found that seminal ROS production was negatively correlated with sperm global DNA methylation, and three-month supplementation with antioxidants produced a significant decrease in seminal ROS and significant increase in sperm global DNA methylation. 24 Additionally, in a study of 61 bladder cancer patients and 45 healthy controls, total antioxidant status in urine was positively correlated with methylation of long interspersed nuclear element-1 (LINE-1) in peripheral blood leukocyte (PBL) DNA from all subjects. 25 To our knowledge, this is the first study to find an association between blood glutathione redox status and global DNA methylation in a generally healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 45 infertile men found that seminal ROS production was negatively correlated with sperm global DNA methylation, and three-month supplementation with antioxidants produced a significant decrease in seminal ROS and significant increase in sperm global DNA methylation. 24 Additionally, in a study of 61 bladder cancer patients and 45 healthy controls, total antioxidant status in urine was positively correlated with methylation of long interspersed nuclear element-1 (LINE-1) in peripheral blood leukocyte (PBL) DNA from all subjects. 25 To our knowledge, this is the first study to find an association between blood glutathione redox status and global DNA methylation in a generally healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation and differentiation of the male germ cells can be disturbed at every level. This may occur as a result of influences that directly or indirectly affect spermatogenesis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for reduced expression of PLCζ could be related to oxidative stress. DNA and RNA are common targets of reactive oxygen species [37] which might have a critical effect on embryo quality and pregnancy rates in IVF/ICSI treatments [38][39][40] and increased upon heat stress or in varicocele condition [30,41].…”
Section: Discussionmentioning
confidence: 99%